The Neural Mechanism of Long-Term Motor Training Affecting Athletes’ Decision-Making Function: An Activation Likelihood Estimation Meta-Analysis - Du, Ying; He, Lingxiao; Wang, Yiyan; Liao, Dengbin (Frontiers in Human Neuroscience, 2022)
Decision-making is an advanced cognitive function that promotes information processes in complex motor situations. In recent years, many neuroimaging studies have assessed the effects of long-term motor training on athletes' decision-making abilities. However, it is controversial whether long-term motor training results in neural network reorganization in athletes and a large amount of data has not been quantitatively summarized until now. Therefore, this study aimed to identify the neural mechanism of long-term motor training affecting the decision-making function of athletes by using activation likelihood estimation (ALE) meta-analysis. Altogether, 12 studies were included and comprised a total of 429 people (219 motor experts and 210 novices, 522 activation foci). The ALE meta-analysis showed that hyperactivation in novices was concentrated in the bilateral occipital lobe, left posterior cerebellar lobe, and left middle temporal gyrus (MTG) in decision-making tasks compared to motor experts. Our results possibly suggested the association between long-term motor training and neural network reorganization in athletes, which provided a reference for further understanding the neural mechanisms of motor decision-making.